From Oppel to Callomon (and beyond): building a high‐resolution ammonite‐based biochronology for the Jurassic System. (11th April 2017) - Page, Kevin N.
Abstract : By 1849, Alcide d'Orbigny had proposed a very modern looking global subdivision of a Jurassique ' System', into a sequence of 10 étage s. D'Orbigny's stages were based on a basic biostratigraphical framework, but there were still a number of issues with its actual demonstrable applicability internationally. In 1856, Albert Oppel took d'Orbigny's framework and, as stated by W.J.Arkell in 1933, ' breath [ed] new life into it … placing the whole science of stratigraphical geology on a new footing '. Oppel recognized eight ' Etagen', divided into a sequence of 'zones' which he considered to be time‐related to correlation units of theoretically universal application – a very clear and unambiguous statement of what now would be considered to be chronostratigraphical practice. Subsequently, evolution of Jurassic stratigraphy had, by the end of the 18th century led to S.S Buckman's high‐resolution ammonite correlation schemes using hemera – essentially the same as modern biohorizons. Although some of this detail was subsequently lost in his syntheses, from around 1933–1956, W.J. Arkell took many pre‐existing 'zonal' schemes and began to develop global 'standard' ammonite correlation schemes – again explicitly chronostratigraphical. Nevertheless, the potential for very high‐resolution ammonite‐based correlation schemes – with a resolution of only around 100, 000 or less – was soon rediscovered and promoted by J.H. Callomon and by a very active 'French School'. Despite all this activity, however, we still have not quite realized the ordered stratigraphical dreams of Oppel and his successors. Of the 11 stages now formally recognized within the Jurassic, four still do not have a ratified GSSP, and within the entire system, there still appear to be no formal agreements on what really are the 'standard' zones for each stage. Crucially, however, confusion is still widespread as to the 'meaning' of these zones – Jurassic 'Standard Zones' are chronozones not biozones – they have been explicitly so since Oppel's day, and as the stratigraphical building blocks of all 'modern' Jurassic stages, they must still be.